REALIZATIONS OF STRATEGIES ENGLISH ONLINE LEARNING TO INCLUSIVE STUDENTS - Rahmad . Husein; Sumarsih . . (LINGUISTIK TERAPAN, 2021)
ABSTRACTLearning strategies is related with specific action taken by english learner and students to make learning process is easier, faster, more enjoyable to new situation. Learning strategies in the beginning used in the military system, but now then also used in education.The aim of this research is to describe similarities and differences with reference to the realizations of learning strategies used in the English online lerning to inclusive students at SMA Negri II Lubuk pakam. This research is conducted by using descriptive qualitative design. The data of this research are sentences containing realization of learning strategies in English online class to inclusive students. The sources of data are taken from 10 inclusive students and 2 English teachers at SMA Negri II Lubuk Pakam grade XI and XII. The inclusive students and English teachers are assumed to represent all inclusive learning both locally and provincially. Each of the learning strategies is represented by ten inclusive students for inclusive students two english teachers for all english teachers in inclusive classes. The data are analyzed by using interactive model in which sentences are analyzed with reference Heaver (2009) theory  adaptation of inclusive learning strategies. The findings indicate that there are similarities and diffrences with reference to the realizations of learning strategies in the English online learning to inclusive students. Keywords: Learning Strategies, English Learning, Online, Inclusive Students